2000
DOI: 10.1074/jbc.m004759200
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of Na,K-ATPase β1 Transcription by Hyperoxia Is Mediated by SP1/SP3 Binding

Abstract: The sodium pump, Na,K-ATPase, is an important protein for maintaining intracellular ion concentration, cellular volume, and ion transport and is regulated both transcriptionally and post-transcriptionally. We previously demonstrated that hyperoxia increased Na,KATPase ␤ 1 gene expression in Madin-Darby canine kidney (MDCK) cells. In this study, we identify a DNA element necessary for up-regulation of the Na,K-ATPase ␤ 1 transcription by hyperoxia and evaluate the nuclear proteins responsible for this up-regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 33 publications
3
16
0
Order By: Relevance
“…Mutation of murine GC/GA elements within the cardiac troponin I promoter produces a four-to fivefold reduction of promoter activity comparable to that seen for the avian cTnT promoter. Putative Sp1 promoter elements have also been shown to be required for optimal activity of cardiac and skeletal ␣-actin, sarco(endo)plasmic Ca 2ϩ -ATPase, and Na ϩ -K ϩ -ATPase ␤ 1 -subunit genes in cultured cells (6,16,24,31,33). These studies do not show direct trans-activation of promoter constructs cotransfected with expressed Sp factors.…”
Section: Sp1 Activates the ϫ268ctnt Promotermentioning
confidence: 68%
“…Mutation of murine GC/GA elements within the cardiac troponin I promoter produces a four-to fivefold reduction of promoter activity comparable to that seen for the avian cTnT promoter. Putative Sp1 promoter elements have also been shown to be required for optimal activity of cardiac and skeletal ␣-actin, sarco(endo)plasmic Ca 2ϩ -ATPase, and Na ϩ -K ϩ -ATPase ␤ 1 -subunit genes in cultured cells (6,16,24,31,33). These studies do not show direct trans-activation of promoter constructs cotransfected with expressed Sp factors.…”
Section: Sp1 Activates the ϫ268ctnt Promotermentioning
confidence: 68%
“…Oxidation of cysteine residues, under conditions of oxidative stress, in zinc fingercontaining transcription factors such as Sp1, result in reduced DNA binding and transcriptional activities (64). Although generally oxidant stress results in reduced Sp1 DNA binding and transcriptional activity, there are instances where oxidant stress increased DNA binding and transcriptional activities of Sp1 and Sp3 to increase promoter activity as in the case of hyperoxia regulation of Na,K-ATPase-␤1 (66). Our data indicated that, although TNF-␣ did not inhibit Sp1 DNA binding activity, it inhibited Sp1 activation of TTF-1 promoter, indicating independent regulation of Sp1 DNA binding activity and promoter activation.…”
Section: Discussionmentioning
confidence: 98%
“…Although Sp1 family members often function to maintain basal transcription rates, Sp1 also plays an important role in regulation of transcription under conditions such as oxidative stress (47). Indeed, in two lung epithelial cell lines and in MDCK cells, the increased transcription of the rat ␤ 1 subunit gene in response to hyperoxia is mediated through increased Sp1 binding (48). Similarly, in neonatal rat cardiac myocytes, the increased rat ␤ 1 subunit transcription rate is associated with increased Sp1 binding (49).…”
Section: Fig 8 Involvement Of the Pkc Pathwaymentioning
confidence: 99%